Killing Two Birds With One Stone: Exposure Simultaneously Addressing Panic Disorder and Obsessive-Compulsive Disorder - Reinecke, A; Hoyer, J (2010)
Massed exposure has gained acceptance as an effective method to treat anxiety disorders. When using this intervention in patients presenting with more than one anxiety disorder, specific treatment options need to be discussed. Should exposure be applied in sequential order for each of the comorbid disorders? Or can exposure sessions also be designed to simultaneously target both problem areas? We report on the cognitive-behavioral treatment of a 28-year-old woman with obsessive-compulsive disorder (OCD) and severe panic disorder with agoraphobia (PDA). A series of behavioral experiments based on prolonged exposure was planned. Due to the fact that avoided situations elicited both agoraphobic and contamination fears, we decided to combine exposure for PDA and OCD to optimize therapeutic transfer. Twelve sessions of this exposure resulted in a long-term reduction of both PDA and OCD symptoms. The case illustrates that two comorbid conditions can be effectively combined under one therapeutic rationale. Capabilities and limitations of the method and implications for current theoretical debates on exposure therapy are discussed. © 2010.